2009
DOI: 10.2337/db07-1298
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and Pharmacological Modulators of ATP-Sensitive K+ Channels Control [Ca2+]c by Different Mechanisms in Isolated Mouse α-Cells

Abstract: OBJECTIVE— We studied how glucose and ATP-sensitive K + (K ATP ) channel modulators affect α-cell [Ca 2+ ] c . RESEARCH DESIGN AND METHODS— GYY mice (expressing enhanced yellow fluorescent protein in α-cells) and NMRI mice were used. [Ca 2+ ] c , the K ATP current (I KATP , perforated mode) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
86
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(111 citation statements)
references
References 53 publications
(102 reference statements)
15
86
2
Order By: Relevance
“…Similar observations have been made in beta cells, which lack functional K ATP channels [4,5]. Our group, as well as others, has shown an apparent disconnect between nutrient-stimulated increase in the ATP/ADP ratio and insulin release [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Although ATP is a critical factor in the control of GSIS, an important question arises from these studies: what are the other important metabolic signalling molecule(s) for insulin secretion?…”
Section: Introductionsupporting
confidence: 67%
“…Similar observations have been made in beta cells, which lack functional K ATP channels [4,5]. Our group, as well as others, has shown an apparent disconnect between nutrient-stimulated increase in the ATP/ADP ratio and insulin release [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Although ATP is a critical factor in the control of GSIS, an important question arises from these studies: what are the other important metabolic signalling molecule(s) for insulin secretion?…”
Section: Introductionsupporting
confidence: 67%
“…The authors confirm that K ATP channel currents are mostly closed in low glucose (0.5 mmol/l) and can be activated by diazoxide or metabolic poisons. To address whether this may be due to increased metabolism in ␣-cells under low glucose conditions, the authors determined changes in the metabolic product NAD(P)H. Levels of NAD(P)H in ␤-cells were found to respond to glucose, as expected; however, ␣-cell NAD(P)H levels did not vary substantially, thereby corroborating previous ␣-cell studies in which equivalent ATP-to-ADP ratios and NAD(P)H or FAD fluorescence under low-and high-glucose conditions were observed (16,17). Thus, this work leads to several important conclusions concerning ␣-cell glucose-sensing mechanisms.…”
supporting
confidence: 69%
“…In summary, the work of Quoix et al provides evidence that the K ATP channel is not the primary ␣-cell target responsible for hypoglycemia-induced glucagon secretion (16). Interestingly, the work also shows that, at least in isolated cells, Zn 2ϩ , insulin, or GABA minimally regulates ␣-cell glucose-induced Ca 2ϩ flux.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Various reports have suggested that stimulation of alpha cells with glucose causes either membrane hyperpolarisation [21] or depolarisation [3,18]. Our recent work demonstrates that, although glucose-dependent inhibition of K ATP channels may not represent a major or sole mechanism contributing to the suppression of glucagon secretion [23], titrating K ATP activity with diazoxide can re-activate alpha cell Ca 2+ signalling and glucagon secretion in the presence of high glucose. While this provides indirect evidence of the involvement of membrane depolarisation in suppression of glucagon secretion [18] and the Ca 2+ and Na + channels involved in action potential depolarisation are clearly subject to voltage-dependent inactivation [3,18], the relationship between membrane depolarisation and termination of alpha cell action potential firing is unclear.…”
Section: Discussionmentioning
confidence: 74%